Влияние дистиллерной жидкости на физико-механические свойства портландцемента - Оразымбетова, Г.Ж; Ерекеева, А.С; Абдисаттарова, Э.А; Рахимов, Г.К; Нурымбетов, Б.Ч (SCIENCE and SOCIETY, 2017)
In the article it is established the increase of the extent of hydration and activity of cements from the clinkers received on the basis of raw mixes with an additi on of production wastes of calcinated soda, especially at joint presence of the phosphate and chloride calcium. The amount of hydrosilicates after the 28th daily curing of ce- ment received according to traditional regulations is 30% lower than when curing the cement received on the basis of clinker from raw mixes with an addition of production wastes of calcinated soda.
Keywords: hydration; cement; clinker; chloride calcium; raw mixes